2019
DOI: 10.1016/j.icarus.2018.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature studies of the rate coefficients and branching ratios of reactive loss vs quenching for the reactions of 1CH2 with C2H6, C2H4, C2H2

Abstract: The kinetics of the reactions of the first excited state of methylene, 1 CH2, with C2H2, C2H4, and C2H6, have been measured over the temperature range 43-298 K by pulsed laser photolysis, monitoring 1 CH2 removal by laser induced fluorescence. Low temperatures were obtained using a pulsed Laval expansion (43-134 K), while a slow flow reaction cell was used for temperatures of 160 K and above. The rate coefficients for the reactions with C2H2, C2H4, and C2H6, all showed a strong negative temperature dependence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…Models The photochemical model is based on previous studies of Titan's photochemistry 46 , updated with high-resolution energy deposition calculations 6 and the latest chemical reaction rates 2,47,48 . The model solves the continuity equation taking into account atmospheric mixing and molecular diffusion, the chemical production and loss processes, and loss/gain due to condensation/evaporation, for each species considered.…”
Section: Methodsmentioning
confidence: 99%
“…Models The photochemical model is based on previous studies of Titan's photochemistry 46 , updated with high-resolution energy deposition calculations 6 and the latest chemical reaction rates 2,47,48 . The model solves the continuity equation taking into account atmospheric mixing and molecular diffusion, the chemical production and loss processes, and loss/gain due to condensation/evaporation, for each species considered.…”
Section: Methodsmentioning
confidence: 99%
“…Versions based on electromagnetic valves supplying gas into the reservoir upstream of the Laval nozzle require very small reservoir volumes (∼1 cm 3 ) owing to the limited flow rate of such valves. Instead of being essentially at rest, the gas is already moving fast and turbulently in the reservoir, impacting the quality of the uniform supersonic flow and limiting the lowest achievable temperature to 43 K. , The use of piezoelectric actuator valves, which allow higher gas flow rates and thus somewhat larger reservoirs, or rotating disk valves, which interrupt the flow close to the Laval throat, enable better quality flows and temperatures as low as 20 and ∼12 K to be achieved, respectively.…”
Section: Laboratory Methods For Measuring Low-temperature Reaction Ki...mentioning
confidence: 99%
“…Using this method, the authors found room temperature branching ratios to H atom channels of (1.08 ± 0.13) and (1.04 ± 0.11) for the reactions of CN with C 2 H 2 and C 2 H 4 , respectively. The H atom calibration technique has been applied to a handful of reactions at T < 300 K: by the group of Seakins and co-workers at the University of Leeds, to study reactions of 1 CH 2 , 26,222 and by Hickson and co-workers at the Universited e Bordeaux for reactions involving C( 3 P), 139,142,144 C( 1 D), 149 and O( 1 D). 158,160 In the former set of experiments, the authors found that the H atom branching ratio for the reaction of 1 CH 2 with both acetylene and ethene increases with temperature between 195 and 298 K. The temperature range was later extended down to 100 K using a pulsed CRESU apparatus, and the H atom branching ratio was shown to continue to decrease at lower temperatures.…”
Section: ■ Product Specific Reaction Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction with pyruvic acid itself is also briefly explored. The rovibrational characteristics and energetics of all critical points on the potential energy surface were characterized at the CCSD(T)/aug-cc-pVTZ//M06-2X-D3/aug-cc-pVTZ level of theory with a wavenumber scaling factor of 0.971 (Zhao and Truhlar, 2008;Dunning, 1989;Purvis and Bartlett, 1982;Grimme et al, 2011; Database of Frequency Scale Factors for Electronic Model Chemistries (Version 4); Alecu et al, 2010). This method compares favourably with the more rigorous focal point analysis of Schreiner et al (2011), with energy differences in the singlet state unimolecular chemistry of less than 0.7 kcal mol −1 , indicating that the method is reliable for kinetic predictions under atmospheric temperatures.…”
Section: Theoretical Analysis Of the Fate Of Singlet Methylhydroxy Carbene Ch 3 Cohmentioning
confidence: 99%